Vegetation sensitivity to droughts (1982-2011) through remote sensing in the Yucatan Peninsula, Mexico - De la Barreda Bautista, Betsabe (2017)
Ecosystems undergo permanent alteration and degradation as a result of the pressure exerted upon them by anthropogenic activities and natural causes. Amongst the natural causes, drought can have considerable impacts on vegetation productivity; these impacts include biomass reduction and changes in vegetation cycles, growth, and vitality. Such impacts have important implications for society, and understanding the impacts of drought in natural systems will help minimise vulnerability to it. The Yucatan Peninsula is a vulnerable area in climate change scenarios, where increased intensity and frequency of droughts is already occurring. This thesis aims to analyse how droughts impact upon vegetation on the Yucatan Peninsula, Mexico using both remotely sensed data (in particular the Advanced Very High Resolution Radiometer – AVHRR - data) and meteorological data (in situ precipitation data). Three major elements are addressed: (1) spatial and temporal precipitation variability, and the occurrence of droughts during the period 1980-2011; (2) vegetation productivity trends, focusing on the persistence and resilience of the different vegetation types present across the Yucatan Peninsula using remotely sensed data sets, specifically, the Normalised Difference Vegetation Index (NDVI) from the National Oceanic and Atmosphere Administration Advanced Very High Resolution Radiometer (NOAA-AVHRR) as a proxy for productivity in the period 1982 to 2011; and (3) the relationship between vegetation productivity and rainfall and the lack of it (i.e. droughts) at a more detailed temporal scale (monthly) with two vegetation indices (NDVI from AVHRR and MTCI from the MEdium Resolution Imaging Spectrometer (MERIS)). The main findings indicate that precipitation in the area follows a gradient from north to south which is linked to vegetation types in the area, from deciduous forest to evergreen forest. NDVI trends in the Yucatan Peninsula are generally stable during the period 1980-2011; however, negative trends are persistent in areas where human impacts and intensive agriculture are present. Analysis of resilience also shows that deciduous forest and grasslands are much less resilient to disturbance and have a longer recovery period compared to other vegetation types. Per-pixel regression analysis between precipitation and vegetation productivity shows high explained variances between NDVI and rainfall with a time-lag of 1 and 2 months and tropical dry forest is the biome most affected by droughts. These results are valuable for decreasing the vulnerability of the Yucatan Peninsula and they could be used for increasing the understanding of the area and therefore go further in the creation of warning and management programmes.